Laser Co2 Radiation Detection Using QWIP - Wail Y. Nassir (Diyala Journal of Engineering Sciences, 2018)
Quantum well infrared photodetector (QWIP) become one of the important devices recently for their efficient, stability,uniformity, and high intrinsic speed. The photodetector was designed, and the validity, absorption coefficient, and band transitions are studied extensively. The quantum wells included in this research operate in mid infrared wavelength region (9-11 µm). Results showed that peak absorption coefficient at (10.6 μm) is (9000 cm-1) for Bound – bound transition and is more narrow and intense from boundcontinuum transition (1800 cm-1) and the quantum well based devices can be used to detect such wavelength providing that the external electric field stays below a reasonable value. This makes such device a promising solution for MIR applications